Potential Application of 4D Technology in Fabrication of Orthodontic Aligners - Elshazly, Tarek M.; Keilig, Ludger; Alkabani, Yasmine; Ghoneima, Ahmed; Abuzayda, Moosa; Talaat, Wael; Talaat, Sameh; Bourauel, Christoph P. (Frontiers in Materials, 2022)
Objectives: To investigate and quantify forces generated by 3D-printed aligners made of shape memory polymers (4D-aligner). Materials and Methods: Clear X v1.1 material was used in this study. On a custom-made typodont model, correction of maxillary central incisor (tooth 21) malposition by 4D aligners with thicknesses (0.8 and 1.0 mm) was measured by superimposition of subsequent scans. Maximum deflection forces generated by foil sheet specimens were measured at different temperatures in 3-point bending tests (3-PB). In a biomechanical system (OMSS), forces generated on movements of (tooth 21) by the 4D aligners were measured at different temperatures. Results: 4D aligners succeeded to achieve a significant tooth movement (2.5±0.5 mm) on the typodont, with insignificant difference between different thicknesses. In 3-PB test, the maximum deflection forces measured at 20, 30, 37, 45, and 55 °C, were 3.8±1.1, 2.5±0.9, 1.7±0.6, 1.0±0.4, and 0.5±0.4 N, respectively. Forces delivered on palatal displacement of (tooth 21) at 37, 45, and 55 ºC by 0.8 mm aligners were 0.3±0.1, 0.2±0.1, and 0.7±0.2 N, respectively. While, by 1.0 mm aligners were 0.3±0.1, 0.3±0.1, and 0.6±0.2 N, respectively. A good concordance with movement on the typodont model was shown in OMSS. Conclusion: Initial study of 4D printed aligner shows its ability to move a tooth by biocompatible orthodontic forces, after a suitable thermal stimulus within the oral temperature range.